The Effectiveness of Learning Accounting Information System with MonsoonSIM - Mahmudi; Aisyah, Maulidyati; Dewi, Herlina Rahmawati; Premarci, Asaquita Sophie (Ilomata International Journal of Tax and Accounting, 2024)
Several accounting education institutions have adopted an experiential learning model through business game simulation to enhance students' ability in understanding course material and increase their competence. MonsoonSIM is a platform that provides business simulations packaged in the form of web-based games that offer students the experience of running a business virtually. This research examines the effectiveness of using MonsoonSIM in increasing student competency in the Accounting Information Systems (AIS) course from the perspective of TAM and UTAUT theory. This study is quantitative research with a survey approach. The sample for this research was 102 students who used MonsoonSIM as a learning medium for the AIS course. This study confirms that Perceived Ease of Use, Facilitating Condition, and Social Influence regarding the use of MonsoonSIM have a positive significant influence on Students’ AIS competence. Then, the higher student’s competence in AIS, the better Students’ Learning Outcome. However, Perceived Usefulness and Perceived Enjoyment of MonsoonSIM do not affect significantly on Students’ AIS Competence. This study support of the use of business game simulation in accounting education institutions to enhance the better understanding of AIS.